The Influence of Entrepreneurial Education on Digital Entrepreneurial Intention through Creativity and Entrepreneurial Self-Efficacy among Generation Z Students in Surabaya - Izzah Rofiatun Nabila; Raya Sulistyowati (Darul Yasin Al Sys, 2026)
High unemployment among university graduates underscores the need to strengthen digital entrepreneurship as an alternative career pathway. Generation Z students possess substantial potential to establish technology-enabled ventures; however, their digital entrepreneurial intention may depend not only on entrepreneurship education but also on creativity and entrepreneurial self-efficacy. This study examines the direct and indirect effects of entrepreneurship education on digital entrepreneurial intention through creativity and entrepreneurial self-efficacy among Generation Z students in Surabaya. A quantitative approach was employed, with data collected through questionnaires from Generation Z students selected using proportionate stratified random sampling. The hypothesized relationships were analyzed using partial least squares structural equation modeling (PLS-SEM). The findings demonstrate that entrepreneurship education has positive and significant effects on digital entrepreneurial intention, creativity, and entrepreneurial self-efficacy. Creativity and entrepreneurial self-efficacy also positively and significantly influence digital entrepreneurial intention. Moreover, both variables mediate the relationship between entrepreneurship education and digital entrepreneurial intention. These findings indicate that entrepreneurship education is more effective in fostering students’ digital entrepreneurial intention when it simultaneously cultivates creative capabilities and confidence in performing entrepreneurial tasks. The study contributes to the digital entrepreneurship literature by clarifying the psychological mechanisms through which entrepreneurship education shapes entrepreneurial intention and provides practical implications for universities seeking to design technology-integrated entrepreneurship programs that strengthen creativity, entrepreneurial self-efficacy, and digital venture creation among Generation Z students.